PHYSICAL ACTIVITY IN ADHD PATIENTS: SIGNIFICANCE, ADVANTAGES, AND EFFECTS OF DIGITAL INTERVENTIONS PROMOTING EXERCISE - Patrycja Jędrzejewska-Rzezak; Monika Czekalska; Natalia Kulicka; Kinga Knutelska; Aleksandra Winsyk; Paulina Gajniak; Maciej Karwat; Tytus Tyralik; Klaudia Bilińska; Joanna Węgrzecka (International Journal of Innovative Technologies in Social Science, 2025)
Attention deficit hyperactivity disorder (ADHD) is among the most commonly diagnosed neurodevelopmental disorders in children, frequently continuing into adulthood. Recent years have witnessed an increasing interest in the importance of physical activity as an adjunctive therapy for controlling ADHD symptoms, including impulsivity, focus difficulties, and hyperactivity. This article aims to review the existing evidence about the effects of physical activity on individuals with ADHD, focusing specifically on contemporary digital methods, including mobile applications, exergaming, virtual reality (VR) technologies, wearable fitness trackers and artificial intelligence (AI) programs. Studies confirm that physical activity improves executive functions, attention, inhibitory control and cognitive flexibility. The article presents the neurobiological mechanisms that elucidate the advantageous effects of exercise on executive functions, together with a review of empirical data validating the efficacy of these interventions. The essay additionally explores the possibility for customizing digital physical activity programs. The findings suggest that physical activity, augmented by digital technologies, can serve as a significant component of a comprehensive ADHD treatment framework, particularly in terms of personalizing therapy and enhancing patient involvement.Materials and methods: A review of the literature available in the PubMed and Google Scholar database was performed, using the key words: “Attention Deficit Hyperactivity Disorder”, “ADHD”, “physical activity”, “digital interventions”, “exergaming”, “virtual reality”, “VR”.